Utilization of Palm Oil Fuel Ash as Binder in Lightweight Oil Palm Shell Geopolymer Concrete - Michael Yong Jing Liu; Choon Peng Chua; U. Johnson Alengaram; Mohd Zamin Jumaat (Advances in Materials Science and Engineering)
Traditionally fly ash (FA) has been used to replace cement as binder in the geopolymer concrete. The utilization of palm oil industrial waste materials known as palm oil fuel ash (POFA) and oil palm shell (OPS) that are abundantly available in South East Asia as binder and coarse aggregate in geopolymer concrete would give an added advantage in both the environmental and economic aspects. The mechanical properties of the OPS geopolymer concrete (OPSGC) through the use of POFA, FA, and OPS are investigated and reported. A total of ten OPSGC mixtures were prepared with varying percentages of POFA and FA such as 0, 10, 20, 40, and 100%. The specimens prepared with two alkaline solution to binder (AK/B) ratios of 0.35 and 0.55 were oven cured at 65°C for 48 hours. The experimental results showed that the highest compressive strength of 30 MPa was obtained for the mix with 20% replacement of FA by POFA and AK/B ratio of 0.55, which underwent oven curing. Further, the mix of up to 20% POFA (with AK/B ratio of 0.55) can be categorized as structural lightweight concrete. An increase of the POFA content beyond 20% decreases the mechanical properties, and hence this mix is recommended to be used.